The Will to Believe in this World: Pragmatism and the Arts of Living on a Precarious Earth. Issue 4 (21st December 2022) - Savransky, Martin
Abstract: The patterns of ecological devastation that mark the present unexpectedly enable an ancient and many‐storied question to resurface with renewed force: the question of the arts of living — that is, of learning how to live and die well with others on a precarious Earth. Modernity has all but forgotten this question, which has long been buried under the dreams of progress and infinite growth, colonial projects, and the enthroning of technoscience. But what might it mean to reclaim the question of the arts of living today? In this article Martin Savransky reclaims the connection between pragmatism, education, and the arts of living by proposing both that (1) William James's pragmatist philosophy can be read as an ongoing and unfinished experiment in weaving a certain art of living, and (2) James's pragmatism might provide us with uniquely generative elements to begin to experiment with the profoundly educational and ecological challenge of learning to inhabit the Earth otherwise.